A vila olímpica Plínio Lemos em Campina Grande-PB e as contradições do planejamento e gestão urbana de espaços públicos - Aguiar, Valmir Bruno de Souza (2023)
The present work aims to analyze the motivations that contributed to the construction, maintenance and attempt to requalify the public space Olympic Village Plínio Lemos, in the city of Campina Grande/PB. Political impasses at the municipal administrative level impact the access to leisure time in the space as a guarantee to the right to the city. The study was constructed around contributions concerning urban policies and the ulterior interventions to the process of requalification in order to investigate the discontinuities and continuities of the urban project proposed for the public space. The research development was grounded on a qualitative analysis, which used the following methodological procedures: the selection of theory-focused literature, field research, semi-structured interviews, direct observation, documental research from public archives of Campina Grande Municipal Secretaries, official documents consultation, e.g. the Official Diaries and Weeklies, Municipal Chamber requirements, government plans, and both printed and digital newspapers, which was examined using the content analysis technique, aside from photographic registers and aerial footage captured by drone. The investigative analysis demonstrated that the public space in the contemporary city is conducted by rooted practices of political dispute, which enable the planning deconfiguration in urban projects, intensifying the degradation of spaces, interrupting the social function of urban equipment, and allowing counter-uses. The emphasis on the study of the Plínio Lemos Olympic Village enables the intensification of discussions over the processes of the reproduction of the urban space, reveling the contradictions expressed by political action managing the public use of space.